2017
DOI: 10.1093/icvts/ivx236
|View full text |Cite
|
Sign up to set email alerts
|

Rotational speed modulation used with continuous-flow left ventricular assist device provides good pulsatility†

Abstract: The co-pulse mode of this novel RS modulation system may provide better pulsatility not only in the large vessels but also in the peripheral vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The impeller speed of the constant speed pattern was the reference speed of the sinusoidal speed pattern. The pulsatile speed pattern waveform was determined using the human aorta waveform, which consisted of the sinusoidal and constant parts, as shown in Equation (5). The reference speed ω 1 of the sinusoidal part was 2400 rpm, and the amplitude A 1 was 400 rpm.…”
Section: Speed Modulation Of the Blood Pump Impellermentioning
confidence: 99%
See 1 more Smart Citation
“…The impeller speed of the constant speed pattern was the reference speed of the sinusoidal speed pattern. The pulsatile speed pattern waveform was determined using the human aorta waveform, which consisted of the sinusoidal and constant parts, as shown in Equation (5). The reference speed ω 1 of the sinusoidal part was 2400 rpm, and the amplitude A 1 was 400 rpm.…”
Section: Speed Modulation Of the Blood Pump Impellermentioning
confidence: 99%
“…Although it has been widely used in clinically treating patients with heart failure and has achieved a good auxiliary effect, some complications still exist, such as bleeding, aortic valve insufficiency, and thrombosis, in patients with heart failure, seriously affecting the treatment effect and the quality of life [3]. Therefore, some studies have explored the possibility that the blood flow rate and pressure at the outlet of CFBP can be similar to the pulsatile-flow output by means of impeller speed modulation [4][5][6], and investigated the differences in the hemodynamic characteristics between a CFBP and a PFBP.…”
Section: Introductionmentioning
confidence: 99%
“…The undulating membrane reproducing blood movement, 11 toroidal flow pump, 12 helical flow device, 13 rotary piston blood pump, 14 shrouded impeller design, 15 and cannulation techniques 16 are all attempting to demonstrate new possibilities and potential benefits over the "classic" centrifugal pumps and existing solutions. Future controller solutions are seeking to enable remote hospital monitoring, more intuitive system interface, optimized control solutions, 17 pump speed modulation, 18 and the potential to use a single controller to automatically control a biventricular assist device configuration. 10 It is important to understand, however, that the uniqueness of any new MCS system will lie in its ability to provide comparable or superior performance with less thrombogenicity in a smaller size (which may allow for use in pediatric patients within device design points) and will preferably be suitable for less-invasive implantation techniques.…”
Section: Progress In Mechanical Circulatory Support: Challenges and Omentioning
confidence: 99%
“…This control method alters rotational speed (RS) of the RBP within a cardiac cycle; for instance, the RS is increased in systole and decreased in diastole, and vice versa. Both experimental and theoretical studies demonstrated that the CBS control can boost pulsatility and reduce load on the LV 12‐15 . Both pulsatility and left ventricular energetics are important indices in management of LVAD patients 16‐18 .…”
Section: Introductionmentioning
confidence: 99%